2020
DOI: 10.5114/pjr.2020.99751
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm thickness and stiffness in patients with hyperkyphosis due to osteoporotic vertebral fracture: an ultrasonographic and elastographic study

Abstract: Purpose The objective of this study was to evaluate the thickness and stiffness of the diaphragm, using ultrasound (US) and strain elastography (SE) in patients with hyperkyphosis due to osteoporotic vertebral fracture. Material and methods This prospective and case-control study was conducted between October 2019 and December 2019. Diaphragm thickness, SE, and strain ratio values of patients with hyperkyphosis due to osteoporotic vertebral fracture were compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The diaphragm is the main respiratory muscle as its movement provides approximately two-thirds of the pulmonary capacity. Correlations between pulmonary function and diaphragmatic ultrasound indices have been reported in some studies, including between FEV1, FVC, and TF in patients with osteoporosis, vertebral fracture, and kyphosis ( 5 ); between MIP, FVC, TF, and DT in patients with late-onset Pompe disease ( 6 ); and between inhalation volume and DM in patients with amyotrophic lateral sclerosis ( 16 ). Moreover, other studies of patients with stroke have reported correlations between DT, thickness ratio, and diaphragm excursion and between FVC, FEV1, and peak expiratory flow ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The diaphragm is the main respiratory muscle as its movement provides approximately two-thirds of the pulmonary capacity. Correlations between pulmonary function and diaphragmatic ultrasound indices have been reported in some studies, including between FEV1, FVC, and TF in patients with osteoporosis, vertebral fracture, and kyphosis ( 5 ); between MIP, FVC, TF, and DT in patients with late-onset Pompe disease ( 6 ); and between inhalation volume and DM in patients with amyotrophic lateral sclerosis ( 16 ). Moreover, other studies of patients with stroke have reported correlations between DT, thickness ratio, and diaphragm excursion and between FVC, FEV1, and peak expiratory flow ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 95%
“…Although it has been reported that the nonparalytic diaphragm increases its movement to compensate for the dysfunction of the paralytic diaphragm, the compensation remains insufficient, resulting in a decrease in the vital capacity of patients with stroke ( 3 , 19–21 , 25 ). In addition to the diaphragmatic muscle, other accessory respiratory muscles, such as the sternocleidomastoid, serratus anterior, and intercostal muscles, may be temporarily or permanently deactivated owing to brain damage ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the mobility of the diaphragm would be impaired. Indeed, Ciloglu et al 41 reported that the diaphragm became thinner and softer at end-inspiration in cases of spinal hyperkyphosis. Moreover, the imposition of negative intrathoracic pressure, caused by diaphragm dysfunction,42 resulted in a reduction in LVEF 43…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the mobility of the diaphragm would be impaired. Indeed, Ciloglu et al 41 reported that the diaphragm became thinner and softer at Copyright r 2023 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%